2019
DOI: 10.1080/14703297.2019.1676284
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and academic performance: The role of compassion and engagement

Abstract: What effects does mindfulness have on university students' academic performance? Our aim in this empirical study is to analyse the relationship between mindfulness and academic performance, and how it might be explained by the role of compassion and engagement. We hypothesise that mindfulness positively relates to academic performance, and that this relationship is mediated by compassion and engagement. The study sample comprises 210 university students from management degrees, who on graduation are likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 34 publications
3
19
2
Order By: Relevance
“…There was also no difference on IECI assessing daily stress, and SPECI, evaluating withdrawal, somatisation, anxiety, dependence, thought problems, attention, hyperactivity, disruptive behaviour, academic performance, depression and violent behaviour. Some prior studies that have demonstrated the role of mindfulness in stress (Costello & Lawler, 2014;van de Weijer-Bergsma et al, 2014), emotional and behavioural regulation (Joyce et al, 2010;Moreno-Gómez et al, 2020;Viglas & Perlman, 2018), and academic performance (Güldal & Satan, 2020;Miralles-Armenteros et al, 2021) on children, but in the present study no differences were detected in these measures. This result may be explained by the fact that both SPECI and IECI baseline data were low before the intervention, meaning that children presented previous low stress levels, and possibly minor emotional and behavioural problems.…”
Section: Discussioncontrasting
confidence: 76%
“…There was also no difference on IECI assessing daily stress, and SPECI, evaluating withdrawal, somatisation, anxiety, dependence, thought problems, attention, hyperactivity, disruptive behaviour, academic performance, depression and violent behaviour. Some prior studies that have demonstrated the role of mindfulness in stress (Costello & Lawler, 2014;van de Weijer-Bergsma et al, 2014), emotional and behavioural regulation (Joyce et al, 2010;Moreno-Gómez et al, 2020;Viglas & Perlman, 2018), and academic performance (Güldal & Satan, 2020;Miralles-Armenteros et al, 2021) on children, but in the present study no differences were detected in these measures. This result may be explained by the fact that both SPECI and IECI baseline data were low before the intervention, meaning that children presented previous low stress levels, and possibly minor emotional and behavioural problems.…”
Section: Discussioncontrasting
confidence: 76%
“…The literature has shown that being compassionate can increase well-being by raising the level of satisfaction derived from the pleasure of helping others [57]. Recent empirical research has found a positive relationship between compassion and academic engagement [58]. Hence, given the importance of encouraging academic engagement, we consider that there is a need for more specific in-depth research into the relationship between compassion and academic engagement.…”
Section: Compassion and Engagementmentioning
confidence: 98%
“…Another analysis indicates that cognitive skills significantly predicted the performance in chemistry, while psychomotor skills and everyday applications had no significant impact on the performance of students (Ramnarain and Ramaila, 2018). Structural equation modeling reveals that compassion partially mediates the relationship between mindfulness and engagement and, consequently, increases academic performance (Miralles-Armenteros et al, 2021).…”
Section: Introductionmentioning
confidence: 96%